Azaindole therapeutic agents. Issue 24 (15th December 2020) - Motati, Damoder Reddy; Amaradhi, Radhika; Ganesh, Thota
Graphical abstract: Abstract: Azaindole structural framework is an integral part of several biologically active natural and synthetic organic molecules; and several FDA approved drugs for various diseases. In the last decade, quite a number of literature reports appeared describing the pharmacology, biological activity and therapeutic applications of a variety of azaindole molecules. This prompted the organic and medicinal chemistry community to develop novel synthetic methods for various azaindoles and test them for a bioactivity against a variety of biological targets. Herein, we have summarized the biological activity of therapeutically advanced clinical candidates and several preclinical candidate drugs that contain azaindole structural moiety.